Different Aspects Women Empowerment and Impact of Financial Inclusion in Empowering Women (International Journal of Innovative Research in Engineering & Management, 2022)
Women are integral part of our society.  Actually, it could be better to say that societies are what  its women are. A woman plays very important role as a  mentor of a kid, as a member of family and as a member  of society. But due to some inappropriate social practices  the society has seen decline in the status and role of  women. The present research has focused upon the  perception of women about themselves after availing the  financial inclusion schemes. The level of awareness about  these schemes have been measured among the women in  selected geographical area. The research has been  concentrated in the Lucknow city. The research focused  three aspects i.e., self-perception, financial strength, and  financial security.
Keywords: Financial Inclusion; Women Empowerment; Social Growth; Financial Security